Clinical and epidemiological profile of patients attendedat home care assistance in Aids – Vitória, ES – Brazil - Casotti, Janaina A.S.; Passos, Luciana N.; Silva, Angela M.C.S.; Tosi, Simone S.F.; Motta, Tânia Q.R. (Brazilian Journal of Sexually Transmitted Diseases, 2004)
Introduction: it’s extremely important the profile study of patients with HIV/AIDS for improvement of assistance, prevention and detection of faults.Objective:knowing clinical and epidemiological profile of HIV/AIDS patients attended in home care program of AIDS (ADT/AIDS). Method: retrospec-tive analyses of charts of patients attended in ADT/AIDS in Vitória metropolitan region. Result: the mean time from diagnostic of HIV until admissionwas 2.5 years, predominant exposition factors were: heterosexual (32.4%) and injecting drug users (28.7%). Locomotion difficulty was reason toADT/AIDS’ assistance in 80% of cases, related with neurotoxoplasmosis and wasting syndrom in 46.6% of times. During the assistance, 66.7% of patientsdidn’t need hospitalization. Before the admission, 47% of patients have been prescribed at least one antiretroviral therapy (HAART), and had changed thismore than two times in 43.5%. After admission, 21% of patients changed HAART more than two times in 27.3% of cases. The median time of staying inADT/AIDS was 64 days, and discharge from the program was for clinical improvement in 41.1% and deads in 49.4% of cases. Conclusion: this studyfound similar profile with the current epidemiology of AIDS that related with heterosexualization, impoverishment and bad level of schooling. Despite theavaliation happened after of HAART era, patients in ADT/AIDS had few time of diagnostic of HIV infection, but they had advanced disease. Therefore,ADT/AIDS have been good alternative of assistance in development countries, leading a reduction of hospitalization and it’s an important mean for com-pliance/adhesion to HAART.